Postfire energy exchange in arctic tundra: the importance and climatic implications of burn severity - ROCHA, ADRIAN V.; SHAVER, GAIUS R. (Global change biology, 2011)
Fires produce land cover changes that have consequences for surface energy balance and temperature. Three eddy covariance towers were setup along a burn severity gradient (i.e. Severely, Moderately, and Unburned tundra) to determine the effect of fire and burn severity on arctic tundra surface energy exchange and temperature for three growing seasons (2008–2010) following the 2007 Anaktuvuk River fire. The three sites were well matched before the fire, experienced similar weather, and had similar energy budget closure, indicating that the measured energy exchange differences between sites were largely attributable to burn severity. Increased burn severity resulted in decreased vegetation and moss cover, organic layer depth, and the rate of postfire vegetation recovery. Albedo and surface greenness steadily recovered with Moderately matching Unburned tundra by the third growing season. Decreased albedo increased net radiation and partly fueled increased latent and ground heat fluxes, soil temperatures, and thaw depth. Decreases in moss cover and the organic layer also influenced the ground thermal regime and increased latent heat fluxes. These changes either offset or decreased the surface warming effect from decreased albedo, resulting in a small surface warming in Severely and a small surface cooling in Moderately relative to Unburned tundra. These results indicate that fires have a significant impact on surface energy balance and highlight the importance of moss and permafrost thaw in regulating arctic surface energy exchange and temperature.